Undercounting File Downloads from Institutional Repositories. Issue 7 (2nd October 2016) - Obrien, Patrick; Arlitsch, Kenning; Sterman, Leila; Mixter, Jeff; Wheeler, Jonathan; Borda, Susan
ABSTRACT: A primary impact metric for institutional repositories (IR) is the number of file downloads, which are commonly measured through third-party Web analytics software. Google Analytics, a free service used by most academic libraries, relies on HTML page tagging to log visitor activity on Google's servers. However, Web aggregators such as Google Scholar link directly to high value content (usually PDF files), bypassing the HTML page and failing to register these direct access events. This article presents evidence of a study of four institutions demonstrating that the majority of IR activity is not counted by page tagging Web analytics software, and proposes a practical solution for significantly improving the reporting relevancy and accuracy of IR performance metrics using Google Analytics.